Strategies For Handling Sleech Delay In Early Childhood - Hartini, Sri (Universitas Sahid Surakarta, 2025)
The age of children 0-6 years is the age of development and growth that greatly determines the child's life in the future. Age 0-6 years is also commonly called the golden age or the golden age as well as the period or period of the child which will determine the next stage of development and growth of children. At this age is the right age for children to take education because at this time children experience an extraordinary process of development and growth. Early childhood is a period of exploration, a period of imitation, a period of sensitivity, a period of play, and a period of early defiance. However, on the other hand, when early childhood is at a critical period which is the golden age of children, it will not be repeated in the next period if its development and potential are not stimulated optimally. One of the disorders experienced by children during their development and growth and most often there is a speech delay (Azizah, 2018). In this dedication, the author provides graphic media activities to children who experience speech delays to stimulate their language development.